2020
DOI: 10.1002/ejhf.1932
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the heart failure through the prism of liver dysfunction

Abstract: This article refers to 'Liver function and prognosis, and influence of sacubitril/valsartan in patients with heart failure with reduced ejection fraction' by K. Suzuki et al., published in this issue on pages 1662-1671.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This observation was not surprising, as multiorgan dysfunction is a well-recognized marker of poor outcome in AHF [7,[24][25][26][27][28]. It has been reported previously that elevated bilirubin is an ominous sign in heart failure [26,[29][30][31][32]. In our study, we observed significantly higher values of total bilirubin at admission in ADHF patients.…”
Section: Discussionsupporting
confidence: 82%
“…This observation was not surprising, as multiorgan dysfunction is a well-recognized marker of poor outcome in AHF [7,[24][25][26][27][28]. It has been reported previously that elevated bilirubin is an ominous sign in heart failure [26,[29][30][31][32]. In our study, we observed significantly higher values of total bilirubin at admission in ADHF patients.…”
Section: Discussionsupporting
confidence: 82%
“…[9,10] Liver dysfunction is prevalent in HF patients, so there has been growing interest in the relationship between the heart and the liver in HF. [11] Sacubitril/valsartan improves measures of liver function compared with enalapril. [12] One study determined the pharmacokinetics and safety of sacubitril/valsartan (LCZ696 [sacubitril/valsartan, Entresto, Novartis, C24H29N5O3.C24H29NO5.5/2H2O.3Na, molecular weight: 915.98]) in patients with mild and moderate hepatic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased liver enzymes in HF, in particular total bilirubin, are independent predictors of worse outcome, thereby, along with higher NT‐proBNP and GDF‐15, reflecting a more diseased patient. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively these biomarkers, combined with an increase in alkaline phosphatase, could originate from liver cell decay, from right‐sided congestion. Moreover, increased liver enzymes in HF, in particular total bilirubin, are independent predictors of worse outcome, thereby, along with higher NT‐proBNP and GDF‐15, reflecting a more diseased patient 11,12 …”
Section: Discussionmentioning
confidence: 99%